Frequencies estimation of gearbox vibration signal based on normalized lattice filter with RLS-based algorithm - Luo, Shunan; Zhang, Feng; Liu, Chao; Zhong, Ray Y (Measurement science & technology, 2021)
In this paper, in order to estimate the meshing frequencies of a gearbox online, based on its vibration signal, an adaptive notch filter with a normalized lattice structure is proposed as an estimator. The notch filter exhibits a high degree of robustness and a low level of estimation errors, due to the minimal dynamic range of the node energies of the normalized lattice structure. A novel lattice recursive least square (NLRLS) algorithm, which introduces a correlation value between the vibration signal and the output signal of the estimation filter into the LRLS algorithm, is used as the adaptive algorithm for the notch filter. Theoretical analysis and simulation results show that the NLRLS algorithm exhibits greater stability than the LRLS algorithm for vibration signals where prior information is lacking. The meshing frequency estimation experiment is performed on a two-stage gearbox experimental platform. A triangular cascade structure is used to connect multiple notch filters to achieve multi-frequency estimation. The experimental results show that the notch filters can estimate meshing frequencies quickly and accurately, which verifies its effectiveness.